Experiences of Discrimination and HIV Risk Among Men Who Have Sex With Men in New York City. (November 2016) - Reilly, Kathleen H.; Neaigus, Alan; Jenness, Samuel M.; Wendel, Travis; Marshall, David M.; Hagan, Holly
The extent of gay-related discrimination in New York City (NYC) and the demographic and behavioral factors correlated with experiences of gay-related discrimination are not well understood. The Centers for Disease Control and Prevention–sponsored National HIV Behavioral Surveillance System, a cross-sectional study, was conducted in NYC in 2011. Men who have sex with men were venue-sampled, interviewed, and offered HIV testing. Frequencies of types of gay-related discrimination experienced in the past 12 months were calculated. Associations between types of discrimination and demographic and HIV risk variables were examined through the estimation of prevalence ratios (PRs) and 95% confidence intervals (CIs). More than half (53.2%) of all study participants reported having experienced any gay-related discrimination in the past 12 months; 45.0% reported that they had been called names or insulted; 23.6% reported receiving poorer services than other people in restaurants, stores, other businesses, or agencies; 22.0% reported being treated unfairly at work or school; 15.1% reported being physically attacked or injured; and 6.7% reported being denied or given lower quality health care. HIV-positive status (adjusted PR [aPR] = 2.9; 95% CI = 1.5, 5.6) and drug use in the past 12 months (aPR = 0.3; 95% CI = 0.1, 0.7) were independently associated with reports of having been denied or given lower quality health care. High rates of reported gay-related discrimination suggest that greater efforts are needed to reduce gay-related discrimination in affected communities. Future research is needed to better understand the extent of gay-related discrimination in NYC, particularly with regard to the relationship between HIV status and health care access.